From Movement to Meaningful Learning: Penguatan Student Engagement dan Keaktifan Peserta Didik melalui Perspektif Deep Learning dan Growth Mindset dalam Pembelajaran PJOK - Jalil Jalil; Alimin Hamzah; Firdaus Sabaruddin (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study aims to analyze the strengthening of student engagement with the perspective of deep learning and growth mindset to increase the activeness of fourth-grade students at UPT SPF SD Inpres Bertingkat Labuang Baji. The study used the Classroom Action Research (CAR) method which was implemented in two cycles, each including the planning stage, action implementation, observation, and reflection. The research subjects were 26 students, consisting of 13 boys and 13 girls. Data were collected through observations using student activeness observation sheets that included participation in movement activities, attention, courage to try, cooperation, response to feedback, and involvement in reflection. Data analysis was carried out descriptively quantitatively by comparing the results at the pre-cycle stage, cycle I, and cycle II. The results showed that the average student activeness increased from 48.20% in the pre-cycle (low category), to 66.75% in cycle I (medium category), and reached 79.40% in cycle II (high category). This improvement demonstrates that the implementation of deep learning supported by a growth mindset perspective can strengthen student engagement through meaningful, collaborative, reflective, and learner-centered learning activities. Thus, the "from movement to meaningful learning" approach is effective in increasing student engagement in physical education (PJOK) while creating a more meaningful learning experience.